2012
DOI: 10.1186/1746-6148-8-18
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of porcine peripheral white blood cells during infection with African swine fever virus

Abstract: BackgroundAfrican swine fever virus (ASFV) is the causative agent of African swine fever (ASF) that is the significant disease of domestic pigs. Several studies showed that ASFV can influence on porcine blood cells in vitro. Thus, we asked ourselves whether ASFV infection results in changes in porcine blood cells in vivo. A series of experiments were performed in order to investigate the effects of ASFV infection on porcine peripheral white blood cells. Nine pigs were inoculated by intramuscular injection with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 21 publications
3
27
1
Order By: Relevance
“…The clinical signs of experimental infection have some differences from those in cited researches with Malawi’ 83 ASFV isolate [9] and our previous study [10]. …”
Section: Resultscontrasting
confidence: 86%
“…The clinical signs of experimental infection have some differences from those in cited researches with Malawi’ 83 ASFV isolate [9] and our previous study [10]. …”
Section: Resultscontrasting
confidence: 86%
“…WBC of NIP (18.16 ± 3.01 × 10 3 /µl) was within the normal range (7 to 20 × 10 3 /µl) for domestic pigs while WBC of hybrid and backcross values of 31.27 ± 1.79 × 10 3 /µl and 27.71 ± 2.01 × 10 3 /µl were higher than the normal range (7 to 20 × 10 3 /µl) ( Table A1 in Appendix). This deviation from normal range for domestic pig was also observed to be in agreement with Karalyan (2012) [17], Anderson (1998) [18] and Eze et al (2010) [19] where the WBC (25.92 ± 8.08 × 10 3 /μl) of the pigs from South-East of Nigeria were higher than the normal or physiological values (7 to 20 × 10 3 /µl). The observed increase in WBC of Hybrid and backcross was adduced to a probable virus inducement of mass-scale mortality of lymphocytes and neutrophils causing the presence of additional nucleus as reported by Karalyan (2012) [17] and Anderson (1998) [18].…”
Section: Leukocyte Traits In Nip Hybrid and Backcrosssupporting
confidence: 77%
“…The observed increase in WBC of Hybrid and backcross was adduced to a probable virus inducement of mass-scale mortality of lymphocytes and neutrophils causing the presence of additional nucleus as reported by Karalyan (2012) [17] and Anderson (1998) [18]. Karalyan (2012) [19] also reported that ASFV infection leads to serious changes in composition of WBC. Stress effects induced due to the presence of pathogen was also presented as a possible cause of increase in WBC [17] [18].…”
Section: Leukocyte Traits In Nip Hybrid and Backcrossmentioning
confidence: 87%
See 1 more Smart Citation
“…It causes acute hemorrhagic fever and leads to high morbidity and mortality with consequent economic losses. There is no available vaccine for ASF (Karalyan et al, 2012). Montgomery was the first to describe ASF, found in Kenya in 1921 (Gil et al, 2008).…”
Section: Introductionmentioning
confidence: 99%